2020
DOI: 10.1098/rspb.2019.2890
|View full text |Cite
|
Sign up to set email alerts
|

Why men invest in non-biological offspring: paternal care and paternity confidence among Himba pastoralists

Abstract: Paternal investment is predicted to be a facultative calculation based on expected fitness returns and modulated by a host of social predictors including paternity uncertainty. However, the direct role of paternity confidence on the patterns of paternal investment is relatively unknown, in part due to a lack of research in populations with high levels of paternity uncertainty. Additionally, much of the work on paternity certainty uses cues of paternity confidence rather than direct assessments from fathers. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…However, this high rate of extra-pair paternity does not always lead to the titration of investment that evolutionary scholars would predict. Both experimental and observational evidence has shown that Himba men place great value on their role as social fathers, even when they suspect they are not the biological father (Prall and Scelza 2020b;Scelza et al 2020a). There is some evidence that spreading paternity across multiple partners positively impacts women's reproductive success, as women who have more children with lovers have overall greater fertility (Scelza 2011a).…”
Section: Concurrent Partnershipsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this high rate of extra-pair paternity does not always lead to the titration of investment that evolutionary scholars would predict. Both experimental and observational evidence has shown that Himba men place great value on their role as social fathers, even when they suspect they are not the biological father (Prall and Scelza 2020b;Scelza et al 2020a). There is some evidence that spreading paternity across multiple partners positively impacts women's reproductive success, as women who have more children with lovers have overall greater fertility (Scelza 2011a).…”
Section: Concurrent Partnershipsmentioning
confidence: 99%
“…Although we do not present data on child labor here, our previous findings lend support to this idea. Himba men have been shown to bias their investments in biological versus non-biological children, in what appears to be a functional response to their productive value (Prall and Scelza 2020b). Girls, who Himba resoundingly praise as being valuable laborers, have poorer anthropometric outcomes when they are believed to be omoka (non-biological offspring).…”
Section: Demography and Economicsmentioning
confidence: 99%
“…Additionally, Shodagor children tend to be watched very closely until around the age of 5, at which point they are often considered proficient swimmers and no longer at risk of drowning, should they fall off of the boat. It is clear that Aka and Shodagor fathers' caregiving are serving different purposes, which is consistent with the facultative nature of human fatherhood, as well as the fact that fathers' contributions to their children vary a great deal across cultures, based on child age (e.g., Crittenden & Marlowe, 2008;Harkness & Super, 1992;Scelza, 2010;Shenk & Scelza, 2012;Shenk et al, 2013;Prall & Scelza, 2020;Winking et al, 2009). Despite limitations with our data, it is clear that Shodagor fathers provide very high levels of direct care for their young children during the dry season, and that fathers in trading households are the primary caregivers of their children more often than mothers, which is a pattern of care that has never before been documented in a subsistencebased society.…”
Section: Shodagor Fathers Provide Very High Levels Of Direct Care (And Sometimes More Than Mothers)mentioning
confidence: 79%
“…What is of particular interest is that EPP is very transparent, with both men and women accurately detecting and accepting cases of EPP (women 72% accuracy; men 73%) (Scelza et al 2020b). The Himba express strong norms associated with fatherhood independent of biological paternity (Prall and Scelza 2020).…”
Section: Paternity Uncertaintymentioning
confidence: 99%